PENDIRIAN KOPERASI BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2012 - , CAKRA PANDU HIMADEWA, Rizky Septiana W, S.H., M.Kn. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Writer choose âCooperation Founding Based on Act Number 17, 2012â as a title, because writer want to more know about cooperation in Indonesia and give more information to other people about cooperation. Writer choose Notary&PPAT Office Nurhadi Darussalam S.H., M.Hum as a place to be Volunteer in there who address in Affandi Street, Bougenville alley, CT X/07 Catur Tunggal, Depok, Sleman, Yogyakarta during 2 (two) months or eight weeks from 03 March 2014 until 02 May 2014. The purpose of this write as a pre-requisite lesson from Law of Diploma Vocational School Gadjah Mada University and then to get âAhli Madya Hukumâ degree (Amd). The benefeit for writer is to give directly experience like a speak up in front of people and get a directly lesson. The result is to found a new cooperative in Indonesia need a minimal 20 (twenty) person as a founder and member, needs âAkta Pendirian Koperasiâ who made from Notary, and also must be signed from Cooperation and UKM Ministry.